Asymmetric Reformatsky-Type Reaction of Isatin-Derived N-Sulfinyl Ketimines: Efficient and Practical Synthesis of Enantiopure Chiral 2-Oxoindolinyl-β3,3-Amino Esters - Su, Lin; Xu, Ming-Hua (Synthesis, 2016)
Optically pure 2-oxoindolinyl-β3,3-amino esters were obtained in good yields via highly efficient diastereoselective asymmetric Reformatsky-type reaction of isatin-derived chiral N-sulfinyl ketimines. The method is practical and allows rapid access to various important synthetic intermediates such as N-free 2-oxoindolinyl-β3,3-amino acid, spiro-β-lactam, and hexahydrofurano[2,3-b]indole. It can also be used for the synthesis of gastrin/cholecyctokinin-B receptor antagonist AG-041R.
Keywords: asymmetric synthesis; β-amino acids; ketimine; oxoindole; Reformatsky reaction; chiral auxiliary; AG-041R